Digitalisasi Kearifan Agraris Menjadi Kompetensi Agripreneurship Murid Pedesaan: Studi Kasus di SMPN 3 Kabuh : Penelitian - Meriena Mustikaning Kussusilo; Anggie Riestanty; Munawaroh (Jurnal Pustaka Cendekia Pendidikan, 2026)
This study aims to describe how the digitalization of agrarian wisdom contributes to the development of agripreneurship competence among rural students at SMPN 3 Kabuh, Jombang Regency. The research employed a descriptive qualitative case study method, in which data were gathered through in-depth interviews, participatory observations of students' digital activities, and portfolio documentation. Data analysis followed the interactive model of data reduction, data display, and conclusion drawing. The findings reveal that the integration of agrarian wisdom is executed by synergizing intra-curricular Social Studies (IPS) with co-curricular activities focused on local tobacco and rain-fed crops. Students utilize contemporary digital commerce practices to acquire practical knowledge related to visual branding, e-commerce management, and social media marketing. Exposure to digital tools enhances students' confidence and problem-solving skills, allowing them to transform traditional farming concepts into competitive business models. The study also finds that agripreneurship interest is shaped by hands-on project experience, environmental awareness, and a supportive school ecosystem. These three components agrarian wisdom integration, digital commerce literacy, and agripreneurship competence are interconnected and mutually reinforcing in preparing rural youth as competitive agribusiness agents.